0012 Peripheral MicroRNAs Are Altered by Total Sleep Deprivation and Psychological Stress and Predict Cognitive Performance in Humans. (27th April 2018) - Zajko, M J; Taylor, D M; Pearson-Leary, J; Bhatnagar, S; Goel, N
Abstract: Introduction: Sleep loss is associated with cancer, cardiovascular disease, and Alzheimer's disease and psychiatric disorders, and also impairs cognitive performance, although there are individual differences in such deficits. MicroRNAs (miRNAs), small non-coding RNAs that are important regulators of gene expression, typically repress expression of their target mRNAs. It remains unknown whether sleep deprivation or the adverse combination of sleep deprivation and psychological stress affect miRNA responses in humans, and whether these responses predict cognitive performance during sleep deprivation. Methods: Thirty-two healthy adults (ages 27–53; mean±SD, 35.1 ± 7.1y; 14 women) participated in a five-day experiment consisting of two 8h time-in-bed (TIB) baseline nights, followed by 39h of total sleep deprivation (TSD) and two 8h-10h TIB recovery nights. A modified Trier Social Stress Test was conducted on the day after TSD to induce psychological stress. The Psychomotor Vigilance Test (PVT), Digit Symbol Substitution Task (DSST), and Digit Span Task (DS), were administered throughout the experiment. Blood samples were taken at 6 time points and miRNAs from plasma were analyzed via Affymetrix microarrays. Linear mixed models with Z-score log2 fold change cutoffs of ±1.645 and greater (FDR<0.05) and pathway analysis using the random forest method were used for statistical analysis. Results: Compared to the pre-study time point, 10 miRNAs showed fold changes with TSD alone and 18 miRNAs showed fold changes with TSD and psychological stress; these miRNAs targeted 2309 and 2823 genes, respectively, with 700 overlapping targets. Notably, at pre study, 14 miRNAs predicted PVT lapses and errors during TSD, 7 miRNAs predicted DSST performance and 10 miRNAs predicted DS performance. Conclusion: For the first time we show that peripheral miRNAs can track responses to total sleep deprivation and its detrimental combination with psychological stress and predict individual differences in cognitive performance. As such, peripheral miRNAs are viable epigenetic biomarkers of sleep deprivation, psychological stress, and cognitive vulnerability in humans. Support (If Any): This work was supported by NASA NNX14AN49G (NG).